PUBLIC-PRIVATE PARTNERSHIP IN GREEN ECONOMY EFFICIENCY - S. N. Khashimova; A. A. Abdikarimova (Journals Park Publishing, 2024)
This article describes the purpose, main tasks of public-private partnership and the system of public-private partnership. The effectiveness of public-private partnerships in the green economy depends on how successfully they contribute to achieving sustainable development, creating new opportunities for business and society, and reducing their negative impact on the environment. In the article, the experience of public-private partnership in the field of green economy can be seen in different countries of the world.
Keywords: Green economy, public-private partnership, private sector, public-private partnership system, public-private partnership project, economic efficiency, risk management.